Pengaruh Penerapan Gamifikasi terhadap Loyalitas Pengguna Grab - Nichora, Marcellino Paskah; Sondari, Mery Citra (Journal of Digital Business Innovation, 2023)
This study aims to explore the impact of implementing gamification on the Grab platform on customer loyalty. The author attempts to link other factors that can influence customer loyalty, such as customer experience, customer engagement, and customer satisfaction. A quantitative approach was used to investigate the impact of gamification on Grab customer loyalty. Online questionnaire was choosen to collect primary data from 257 respondents. The findings from the analysis of data using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method have uncovered important insights regarding the connection between gamification and customer loyalty. The research results indicate that while gamification on the Grab platform has a direct impact on customer loyalty, it is not statistically significant. However, gamification does significantly influence customer loyalty through three intermediary variables: customer experience, customer satisfaction, and customer engagement. This implies that the utilization of gamification by Grab indirectly shapes how customers engage with the platform, their perception of satisfaction with the provided services, and the depth of their involvement in activities with Grab.